Extinction Dynamics Under Extreme Conservation Threat: The Flora of St Helena - Lambdon, Phil; Cronk, Quentin (Frontiers in Ecology and Evolution, 2020)
The flora of the island of St Helena provides an amplified system for the study of extinction by reason of the island’s high endemism, small size, vulnerable biota, length of time of severe disturbance (since 1502) and severity of threats. Endemic plants have been eliminated from 96.5% of St Helena by habitat loss. There are eight recorded extinctions in the vascular flora since 1771 giving an extinction rate of 581 extinctions per million species per year (E/MSY). This is considerably higher than background extinction rates, variously estimated at 1 or 0.1 E/MSY. We have no information for plant extinctions prior to 1771 but applying the same extinction rate to the period 1502 to 1771 suggests that there may be around ten unrecorded historical extinctions. We use census data and population decline estimates to project likely extinction forward in time. The projected overall extinction rate for the next 200 years is somewhat higher at 625 E/MSY. However, our data predict an extinction crunch in the next 50 years with 4 species out of the remaining 48 likely to become extinct during this period. It is interesting that during a period when the native plant areas dropped to 3.5% of the original, the extinction rate appears to have remained shallowly linear with under 30% of the endemic flora becoming extinct.